All-Ukrainian student olympiad from the educational discipline "Histology, cytology, embryology" - Editorial office of journal "Morphologia" (Морфологія, 2018)
On April 17-20, 2018, the 2nd stage of the All-Ukrainian Student Olympiad on the academic discipline "Histology, Cytology, Embryology" was held on the basis of the Ukrainian State Medical School "Ukrainian Medical Dentistry Academy".